1994
DOI: 10.1523/jneurosci.14-03-01290.1994
|View full text |Cite
|
Sign up to set email alerts
|

Physiological properties of vestibular primary afferents that mediate motor learning and normal performance of the vestibulo-ocular reflex in monkeys

Abstract: We have used electrical stimulation of the vestibular apparatus to reveal parallels between the physiological responses of the vestibular afferents activated at different currents and the properties of the evoked eye movements before and after magnifying spectacles had been used to cause motor learning in the vestibulo-ocular reflex (VOR). Stimulation with the lowest currents caused little or no eye motion, but activated all the afferents with irregular spontaneous discharge, low sensitivities to head velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 33 publications
2
14
0
1
Order By: Relevance
“…The timecourse of the response to current steps varied across MVN neurons, suggesting that some of the differences in response dynamics in vivo could arise from intrinsic membrane properties. However, vestibular afferents also display a wide range of response dynamics (Bronte-Stewart and Lisberger 1994;Fernandez and Goldberg 1971), consistent with the possibility that response dynamics of MVN neurons in vivo could also be conferred by the signals present in their afferent inputs.…”
Section: Comparisons Of Mvn Neurons In Vivo and In Vitrosupporting
confidence: 59%
“…The timecourse of the response to current steps varied across MVN neurons, suggesting that some of the differences in response dynamics in vivo could arise from intrinsic membrane properties. However, vestibular afferents also display a wide range of response dynamics (Bronte-Stewart and Lisberger 1994;Fernandez and Goldberg 1971), consistent with the possibility that response dynamics of MVN neurons in vivo could also be conferred by the signals present in their afferent inputs.…”
Section: Comparisons Of Mvn Neurons In Vivo and In Vitrosupporting
confidence: 59%
“…Prior analyses have suggested that the inputs to the VOR interneurons come from a diverse group of afferents (Highstein et al 1987) that are centered roughly in the middle of the distribution of dynamic response properties (Bronte-Stewart and Lisberger 1994;Minor and Goldberg 1991). Further, prior data suggest that the vestibular inputs to the unmodified pathways may have somewhat more phase lead compared with inputs to the modified pathways (Lisberger and Pavelko 1986;Lisberger et al 1994b).…”
Section: Sources Of Phase Shifts Of Ftns and Pvpsmentioning
confidence: 99%
“…Almost all VO neurons, for example, fire at shock strengths that only recruit irregular afferents (Goldberg et al 1994), yet these neurons are known to receive a significant regular input Boyle et al 1992). The interpretation of the effects of single shocks on the operation of multisynaptic pathways is even more difficult as it raises the need to specify the transformation between synaptic input and firing at several sites (Brontë-Stewart and Lisberger 1994).…”
Section: Central Mechanisms Central Terminations Of Vestibular-nerve mentioning
confidence: 99%
“…The second EPSP has a low threshold, but continues to grow as shock strength increases. Characteristics of regularly and irregularly discharging afferents, mammalian vestibular nerve High thresholds and small responses to the same galvanic stimuli a Goldberg and Fernández 1977;Yagi et al 1977;Baird et al 1988;Goldberg et al 1990a;Lysakowski et al 1995 b Goldberg andFernández 1971b;Yagi et al 1977;Fernández and Goldberg 1976b;Baird et al 1988;Goldberg et al 1990a;Lysakowski et al 1995 c Goldberg andFernández 1980;McCue andGuinan 1994 d Ezure et al 1983;Goldberg et al 1982Goldberg et al , 1984Goldberg et al , 1987Brontë-Stewart and Lisberger 1994 …”
mentioning
confidence: 99%